THERMOCHEMICAL FUEL CONVERSION IN MARINE POWER SYSTEMS: MODELING AND EFFICIENCY ANALYSIS - Косоруков, Єгор (SWorldJournal, 2025)
This paper presents a comprehensive study on the thermochemical conversion of hydrocarbon fuels using non-catalytic steam reforming for advanced energy systems. The research focuses on evaluating energy gain from fuel processing and explores mathematical